Neisseria Gonorrhoeae Modulates Immunity by Polarizing Human Macrophages to a m2 Profile - Imarai-Bahamonde, C; Acuna-Castillo, C (Public Library of Science, 2015)
Current data suggest that Neisseria gonorrhoeae is able to suppress the protective immune response at different levels, such as B and T lymphocytes and antigen-presenting cells. The present report is focused on gonococcus evasion mechanism on macrophages (MΦ) and its impact in the subsequent immune response. In response to various signals MΦ may undergo classical-M1 (M1-MΦ) or alternative-M2 (M2-MΦ) activation. Until now there are no reports of the gonococcus effects on human MΦ polarization. We assessed the phagocytic ability of monocyte-derived MΦ (MDM) upon gonococcal infection by immunofluorescence and gentamicin protection experiments. Then, we evaluated cytokine profile and M1/ M2 specific-surface markers on MΦ challenged with N. gonorrhoeae and their proliferative effect on T cells. Our findings lead us to suggest N. gonorrhoeae stimulates a M2-MΦ phenotype in which some of the M2b and none of the M1-MΦ-associated markers are induced. Interestingly, N. gonorrhoeae exposure leads to upregulation of a Programmed Death Ligand 1 (PD-L1), widely known as an immunosuppressive molecule. Moreover, functional results showed that N. gonorrhoeae-treated MΦ are unable to induce proliferation of human T-cells, suggesting a more likely regulatory phenotype. Taken together, our data show that N. gonorroheae interferes with MΦ polarization. This study has important implications for understanding the mechanisms of clearance versus long-term persistence of N. gonorroheae infection and might be applicable for the development of new therapeutic strategies. © 2015 Ortiz et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.